Some Data Dependence Results From Using $\mathcal{C}$-Class Functions in Partial Metric Spaces - Abdessalem Benterki (Universal Journal of Mathematics and Applications)
This research paper examines the data dependence of fixed point sets for pseudo-contractive multifunctions in partial metric spaces using the notion of $\mathcal{C}$-class functions. By building upon previous findings from the literature, this work sheds more light on some new perspectives as well as generalizations on this issue. To illustrate how the $\mathcal{C}$-class function can be applied to study the data dependence of fixed point sets for a certain pseudo-contractive multifunction, an illustrative example is given.